PENGARUH PELAYANAN PRIMA, KONSULTASI ACCOUNT REPRESENTATIVE, DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN FORMAL(STUDI PADA WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA SURABAYA SUKOMANUNGGAL) - PUTRI AFRILIA IRIANTI, DYA (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACTThe aim of this research is to determine the effect of the prime service quality of taxation, the effectiveness of Account Representative consultation and taxation awareness to individual taxpayer’s formal compliance in Small Taxpayers Office Surabaya Sukomanunggal. This research used quantitative approach with the primary data obtained from questionnaires. The sample that got from one hundred individual taxpayers that registered in Small Taxpayers Office Surabaya Sukomanunggal. This research used multiple linear regression analysis with the program SPSS 21. The result of this research shows that the prime service quality of taxation, the effectiveness of Account Representative consultation, and taxation awareness has positive influence toward individual taxpayer’s formal compliance in Small Taxpayers Office Surabaya Sukomanunggal. Key Words: Individual taxpayer’s formal compliance, prime service quality of taxation, Account representative consultation, taxation awareness.